The impact of war on the labor market in Ukraine - Цимбалюк, Ірина Олександрівна; Tsymbaliuk, Iryna (Луцьк : Вежа-Друк, 2023)
The war that broke out in Ukraine has resulted in irreparable damage and has had a severe impact on the countryʼs economy. Millions of people have lost their jobs, and the labor market has undergone significant changes. Russiaʼs invasion of Ukraine has caused the deepest crisis in the labor market, reducing the number of jobs and leading to an extraordinary increase in unemployment.
Вплив війни на ринок праці в Україні
Keywords: ринок праці; зайнятість; війна в Україні; labor market; economic activity; unemployment rate in Ukraine; 331.5-029:3